Governance Strategies for Conducting Text Messaging Interventions in Clinical Research. Issue 2 (28th April 2014) - Anderson, Nicholas; Morrison, Caitlin; Griffin, Jonathan; Reiter, William; Baldwin, Laura‐Mae; Edwards, Kelly
Abstract: There is increasing interest in medical text messaging interventions being used to achieve positive patient outcomes across a range of clinical research and health practice environments. Short messaging service (SMS) is a low‐cost tool that provides an easy communication route to engage potentially broad populations through text messaging, and is part of the growing social trend toward increased adoption of personal communication technologies by patient populations. Testing the effectiveness and impact of various communication strategies requires navigation of a complex web of clinical and research regulations and oversight mechanisms. We describe a case study of the implementation of SMS to provide bidirectional communications between physicians and patients involved in routine care reminders to illustrate the review processes and governance structures needed. By mapping the regulatory and approval processes required to manage and steward a research study across clinical and community boundaries, we provide a guide for other translational health researchers who may utilize similar kinds of personally owned technology interventions as research tools.